2018
DOI: 10.1111/iere.12286
|View full text |Cite
|
Sign up to set email alerts
|

Entry Regulations, Welfare, and Determinants of Market Structure

Abstract: Welfare effects of entry regulations are theoretically ambiguous in differentiated product markets. We use a dynamic oligopoly model of entry and exit with store-type differentiation and static price setting to evaluate how entry regulations affect long-run profitability, market structure, and welfare. Based on unique data for all retail food stores in Sweden, we estimate demand, recover variable profits, and estimate entry costs and fixed costs by store type. Counterfactual policy experiments show that welfar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 62 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…D. McGowan (2014) found that a higher level of barriers to entry helps avoid creative destruction processes; in other words, they encourage inefficient companies to remain in the market. Similar results are offered by Maican and Orth (2018) in the food sector in Sweden. Based on the empirical review presented, the following hypothesis is proposed:…”
Section: Industry Characteristicssupporting
confidence: 80%
“…D. McGowan (2014) found that a higher level of barriers to entry helps avoid creative destruction processes; in other words, they encourage inefficient companies to remain in the market. Similar results are offered by Maican and Orth (2018) in the food sector in Sweden. Based on the empirical review presented, the following hypothesis is proposed:…”
Section: Industry Characteristicssupporting
confidence: 80%
“…Another limitation of our study is that it does not evaluate the impact of FBR on consumer welfare, the employment effect beyond those of mom-and-pop stores, and industry productivity. Illustratively, it is possible that consumers in FBR cities pay higher prices due to the lack of competition and that existing research has demonstrated that other forms of entry barriers could be harmful to consumer welfare (Maican & Orth, 2018). These broader economic implications are highly important to understand the comprehensive impacts of chain store entry barriers and thus should be subject to future research on FBR.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Entry costs reduction in the formal sector has weaker effect on the decrease of informality, yet strong positive effect on welfare gains, GDP growth and wages. Similarly, Maican and Orth (2018) analyze Swedish retail food stores data and establish that, by enhancing competition, lower entry costs increase welfare in differentiated product markets.…”
Section: Business Reformsmentioning
confidence: 99%